Stable Zinc Anodes Enabled by Zincophilic Cu Nanowire Networks - Xie, Shiyin; Li, Yang; Li, Xu; Zhou, Yujun; Dang, Ziqi; Rong, Jianhua; Dong, Liubing (Nano-Micro Letters, 2021)
Zn-based electrochemical energy storage (EES) systems have received tremendous attention in recent years, but their zinc anodes are seriously plagued by the issues of zinc dendrite and side reactions (e.g., corrosion and hydrogen evolution). Herein, we report a novel strategy of employing zincophilic Cu nanowire networks to stabilize zinc anodes from multiple aspects. According to experimental results, COMSOL simulation and density functional theory calculations, the Cu nanowire networks covering on zinc anode surface not only homogenize the surface electric field and Zn2+ concentration field, but also inhibit side reactions through their hydrophobic feature. Meanwhile, facets and edge sites of the Cu nanowires, especially the latter ones, are revealed to be highly zincophilic to induce uniform zinc nucleation/deposition. Consequently, the Cu nanowire networks-protected zinc anodes exhibit an ultralong cycle life of over 2800 h and also can continuously operate for hundreds of hours even at very large charge/discharge currents and areal capacities (e.g., 10 mA cm−2 and 5 mAh cm−2), remarkably superior to bare zinc anodes and most of currently reported zinc anodes, thereby enabling Zn-based EES devices to possess high capacity, 16,000-cycle lifespan and rapid charge/discharge ability. This work provides new thoughts to realize long-life and high-rate zinc anodes. Highlights: 1 A novel strategy of employing Cu nanowire networks to realize superior long-life and high-rate zinc anodes was proposed. 2 Cu nanowire networks could stabilize zinc anodes from multiple aspects, including homogenizing surface electric field and Zn2+ concentration field, inhibiting side reactions and inducing uniform zinc nucleation/deposition. 3 Facets and edge sites of Cu nanowires, especially the latter ones, were revealed to be highly zincophilic.